1998
DOI: 10.1128/aem.64.3.940-947.1998
|View full text |Cite
|
Sign up to set email alerts
|

Complete Reductive Dehalogenation of Brominated Biphenyls by Anaerobic Microorganisms in Sediment

Abstract: We sought to determine whether microorganisms from the polychlorinated biphenyl (PCB)-contaminated sediment in Woods Pond (Lenox, Mass.) could dehalogenate brominated biphenyls. The PCB dechlorination specificities for the microorganisms in this sediment have been well characterized. This allowed us to compare the dehalogenation specificities for brominated biphenyls and chlorinated biphenyls within a single sediment. Anaerobic sediment microcosms were incubated separately at 25°C with 16 different mono- to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…Based on their findings, these authors proposed that PCB-dechlorinating microorganisms might be able to dehalogenate brominated biphenyls. Likewise, we recently found that the anaerobic microorganisms in Woods Pond sediment can dehalogenate many mono-, di-, and tribrominated biphenyls even though the upper Housatonic River has no history of contamination with brominated biphenyls (6). Our data suggested that PCB-dehalogenating microorganisms in Woods Pond might exhibit relaxed specificity for brominated biphenyl dehalogenation.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Based on their findings, these authors proposed that PCB-dechlorinating microorganisms might be able to dehalogenate brominated biphenyls. Likewise, we recently found that the anaerobic microorganisms in Woods Pond sediment can dehalogenate many mono-, di-, and tribrominated biphenyls even though the upper Housatonic River has no history of contamination with brominated biphenyls (6). Our data suggested that PCB-dehalogenating microorganisms in Woods Pond might exhibit relaxed specificity for brominated biphenyl dehalogenation.…”
supporting
confidence: 60%
“…Therefore, when referring to halogenated biphenyls, we use the term micromolar (M) to mean micromoles per liter of slurry. In most cases, disodium malate was also added to a final concentration of 10 mM because previous experiments showed that malate accelerated dehalogenation (6). No other nutrients were added.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many brominated pollutants, such as brominated biphenyls and tetrabromobisphenol A are ubiquitously present in the environment and reductive dehalogenation is considered crucial in their biodegradation (e.g., Bedard and Van Dort, 1998;Voordeckers et al, 2002;Liu et al, 2013). Reductive debromination has been observed in sediment microcosms (e.g., Monserrate and H€ aggblom, 1997), and some bacteria are reported with reductive debromination ability, for example, a highly enriched Dehalococcoides culture was able to debrominate polybrominated diphenyl ethers, tetrabromobisphenol A and other phenolic bromoaromatics (He et al, 2006;Lee et al, 2011;Cooper et al, 2015;Yang et al, 2015), and Desulfovibrio strains and Desulfobacterium chlororespirans are reported to debrominate brominated phenolics (Boyle et al, 1999;Fennell et al, 2004;Cupples et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies available on the microbial dehalogenation of brominated compounds, bromine substituents seem to be easier removable than chlorine substituents (Wu and Wiegel, 1997;Bedard and Van Dort, 1998;Boyle et al, 1999;Voordeckers et al, 2002). This may be partially due to the more labile nature of the carbon-bromine bond (Vogel et al, 1987;Allard and Neilson, 2003); also, debromination is thermodynamically more favourable than dechlorination (Dolfing, 2003).…”
Section: Reductive Debromination Of 12-dibromoethene In Culturesmentioning
confidence: 99%